Role related stress and job satisfaction among school counselors in Lebanon - Yassen, Manal Hassan (Beirut American University of Beirut. Faculty of Arts and Sciences, 2013)
The review of the literature revealed that there is little research on guidance and counseling in schools in Lebanon regarding role-related stress and job satisfaction therefore this gap was addressed through investigating the following: a) level of job-related stress and its various components of Lebanese counselors by class level (elementary, middle and secondary), b) difference, if any, by level for role-related stress and its components i.e. role conflict and role ambiguity, c) if professional characteristics such as years of counselors counseling and teaching experience, type of employment (full time or part time) and initial perception of the job are related to role stress d) the relationship of role related stress and its components to job satisfaction. A sample of (27) counselors from all grade levels in private schools in greater Beirut participated in this study. Participants responded to two questionnaires, which are Role Questionnaire and Satisfaction Questionnaire. Results revealed that there is role conflict; role ambiguity and role stress amongst the school counselors from all levels. It was reported that elementary school counselors have higher role conflict, ambiguity and stress than secondary school counselors; however, the difference among levels is insignificant. It was also reported that experience as a school counselor and initial perception of the job is significantly related to job stress. Finally, role stress was found to have a significant and negative correlation to job satisfaction. Further implications to practice were recommended.
: Mémoire
Keywords: Job Satisfaction School guidance and counseling; Orientation et Conseil; Satisfaction professionnelle